Assessing an evidence-based intervention for spouse caregivers of persons with Alzheimer's disease: results of a community implementation of the NYUCI in Israel. (2nd September 2021) - Werner, Perla; Clay, Olivio J.; Goldstein, Dovrat; Kermel-Schifmann, Ile; Herz, Michal Karen; Epstein, Cynthia; Mittelman, Mary S.
Abstract: Objectives: Alzheimer's disease (AD) affects not only the person with the illness, but family caregivers as well. The NYU Caregiver Intervention (NYUCI), a psychosocial intervention which has demonstrated both short and long-term benefits for caregivers, has been used widely in the United States and in Australia and England. The Israeli study was a hybrid between a community implementation study and a randomized controlled trial (RCT) of the NYUCI in a non-English speaking country. Method: A sample of 100 spouse caregivers participated in trial comparing the NYUCI provided by ten Israeli clinicians (enhanced care), to support group participation (usual care). The major outcome of interest was caregiver depressive symptoms, measured with the Geriatric Depression Scale. A linear random effects regression model controlling for factors associated with depressive symptoms was used to plot the longitudinal trajectories of depressive symptoms over the two-year study period and compare outcomes for the enhanced care and control groups. Results: One hundred spouse caregivers enrolled, of whom 81 provided data at baseline and at one or more post intervention assessments. The Israeli adaptation of the NYUCI was effective in reducing depressive symptoms reported by caregivers compared to their counterparts in the control group, b= −1.29 [95%CI (−2.43, −0.15)], p = .0265. Conclusion: While implementing a randomized controlled trial of an intervention developed and tested in traditional research settings using community providers in Israel, posed unique challenges, the study demonstrated benefits to caregivers. As a result, 30 municipalities in Israel are currently implementing an ongoing adaptation of the NYUCI.